Penerapan Model Pembelajaran Problem Solving Dengan Pendekatan Saintifik Pada Kemampuan Penalaran Matematis Siswa Kelas VIII B SMP Negeri 1 Padamara - Dyah Ayu Nur Khoeriyah; Ahmad Ahmad (AlphaMath : Journal of Mathematics Education, 2020)
This study aims to improve students' mathematical reasoning abilities in learning mathematics through Problem Solving with Scientific approaches. The subjects in this study were all students of class VIII B, Padamara 1 st junior high school, totaling 33 students. This research was conducted in 3 cycles, each cycle consisting of 2 meetings. Each cycle in this study includes action planning, action implementation, observation and reflection. To measure the ability of mathematical reasoning is evaluated using the mathematical reasoning ability test. Based on the results of the study, the mathematical reasoning ability of the first cycle obtained an average value of 40.9, the second cycle obtained an average value of 60.15, and the third cycle obtained an average value of 63.3. The conclusion obtained from this study is that learning with Problem Solving with the Scientific approach can improve the mathematical reasoning ability of students of class VIII B Padamara 1 N Middle School, especially the subject of Building a Flat Side Room.